Microbiology of Fermented Foods and Beverages - Varzakas, Theodoros (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Fermented foods are consumed all over the world and their consumption shows an increasing trend. They play many roles, from preservation to food security, improved nutrition and social well-being. Different microorganisms are involved in the fermentation process and the diversity of the microbiome is high.Fermented foods are food substrates that are invaded or overgrown by edible microorganisms whose enzymes hydrolyze polysaccharides, proteins and lipids to nontoxic products with flavors, aromas, and textures that are pleasant and attractive to the human consumer. Fermentation plays different roles in food processing, including the development of a wide diversity of flavors, aromas, and textures in food, lactic acid, alcoholic, acetic acid, alkaline and high salt fermentations for food preservation purposes, biological enrichment of food substrates with vitamins, protein, essential amino acids, and essential fatty acids and detoxification during food fermentation processing.